2017
DOI: 10.1183/13993003.00651-2017
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure response to CPAP treatment in subjects with obstructive sleep apnoea: the predictive value of 24-h ambulatory blood pressure monitoring

Abstract: The reduction in blood pressure (BP) with continuous positive airway pressure (CPAP) is modest and highly variable. In this study, we identified the variables that predict BP response to CPAP.24-h ambulatory BP monitoring (ABPM), C-reactive protein (CRP), leptin, adiponectin and 24-h urinary catecholamine were measured before and after 6 months of CPAP in obstructive sleep apnoea (OSA) patients.Overall, 88 middle-aged, obese male patients with severe OSA (median apnoea-hypopnoea index 42 events·h) were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 40 publications
2
35
1
1
Order By: Relevance
“…However, an increase in sympathetic activity in individuals with OSA is supported by our finding of a 14% reduction in mean 24‐hour urinary norepinephrine at follow‐up among all PAP‐adherent OSA participants. Previous studies report decreases in urinary norepinephrine excretion of similar magnitude . Extending those findings, our results, controlling for baseline AHI, indicate that OSA participants who are obese have the greatest reduction in urinary norepinephrine excretion following PAP treatment.…”
Section: Discussionsupporting
confidence: 86%
“…However, an increase in sympathetic activity in individuals with OSA is supported by our finding of a 14% reduction in mean 24‐hour urinary norepinephrine at follow‐up among all PAP‐adherent OSA participants. Previous studies report decreases in urinary norepinephrine excretion of similar magnitude . Extending those findings, our results, controlling for baseline AHI, indicate that OSA participants who are obese have the greatest reduction in urinary norepinephrine excretion following PAP treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Factors like normal baseline BP [6], mild respiratory disorders [4], low cardiovascular responsiveness to autonomic activation [7] or lack of sleepiness [8], may attenuate the effect of apnoea abolition or give rise to unexpected findings. For example, some authors have described a small increase in nocturnal BP in some OSA patients [9,10], and hypothesised the existence of some "OSA phenotypes" with specific BP responses to CPAP [9]. Identification of such phenotypes would be helpful for better and individualised patient management.…”
mentioning
confidence: 99%
“…First, an abnormal BP dipping pattern is a predictor of cardiovascular events, and a previous study showed that this BP pattern's manifestation during ambulatory BP monitoring is a good predictor of BP response to CPAP. 9 Second, participants recruited in the SAVE trial comprised patients with previous coronary or cerebrovascular disease. Not all patients had hypertension (and most of them had BP controlled at baseline, as suggested by the baseline characteristics).…”
mentioning
confidence: 99%